Sistemas semidinâmicos impulsivos - Nolasco, Victor Hugo (2013)
This work is an introduction the theory of impulsive semidynamical systems. Impulsive systems are a natural generalization of the classical theory of continuous semidynamical systems. First chapter presents the theory of continuous semidynamical systems. The second chapter is devoted to impulsive semidynamical systems theory. In this chapter, we study some properties of the impulsive systems. Interested in studying the asymptotic behavior of a impulsive semidynamical systems, in the third and fourth chapters of this work concepts like invariance, dissipativity and global attractor are presented. The study of these concepts for impulsive systems provides us with assurances that a particular process approaches of a standard in the future. Moreover, the center of Levinson is defined for compact dissipative impulsive semidynamical systems and some of it’s topological properties, for example, compactness and connectedness are studied.